Cold-formed high strength steel SHS and RHS beams at elevated temperatures. (July 2019) - Li, Hai-Ting; Young, Ben
Abstract: The structural responses of cold-formed high strength steel (HSS) square and rectangular hollow section (SHS and RHS) beams at elevated temperatures were examined in this study. Stress-strain relationships of cold-formed HSS at elevated temperatures were proposed and verified against material test results. The proposed stress-strain relationships were then employed in a finite element (FE) analysis to study the behaviour of cold-formed HSS SHS/RHS beams at elevated temperatures up to 1000 °C. The developed FE model was verified with available test results of cold-formed HSS SHS/RHS beams; upon verification, a total of 252 numerical flexural capacities were gained from FE analyses. The numerical results were used to investigate the suitability of existing cross-section slenderness limits to the HSS tubular sections at elevated temperatures. The applicability of current flexural design provisions in the Eurocode 3, AISC and AISI specifications to the investigated HSS tubular beams at elevated temperatures was also examined. Overall, it is shown that the codified provisions can provide quite conservative predictions; an improved design rule is proposed by modifying the direct strength method (DSM) in the AISI specification. Furthermore, reliability analyses were carried out to assess reliability levels of codified and modified provisions. It has been demonstrated that the modified DSM can produce accurate and reliable design and therefore is recommended to be used for cold-formed HSS SHS/RHS beams at elevated temperatures. Highlights: Cold-formed high strength steel SHS and RHS beams at elevated temperatures were examined. A constitutive model is proposed to predict stress-strain curves at elevated temperatures. A total of 252 beams were subjected to various temperatures up to 1000 °C. Existing slenderness limits for sections subjected to bending are assessed. Codified design provisions are evaluated and improved design rules are proposed.